Hydrogen generation from renewables: Steam reforming of ethanol and dimethyl ether over structured catalysts - Ledesma, Cristian (2009)
Ethanol and dimethyl ether can be efficiently reformed with steam over appropriate catalysts for generating hydrogen. Both substrates provide a valuable example of the use of renewable chemicals for energy applications. At temperatures as low as 623 K, a mixture of ethanol and water at S/C=1.5 can yield as much as 92 percent H2 over honeycomb structures coated with cobalt-based catalyst layers, with only 1 percent carbon monoxide. Dimethyl ether can be similarly reformed at 823 K. At S/C=1.5, hydrogen yields up to 80 percent are obtained over honeycombs coated with copper-zinc supported over ZrO2. The performance of these systems improves considerably by using microreaction technologies, not only by increasing the surface-to-volume ratio, but also for allowing autothermal regimes.